Pemanfaatan Bangunan Bekas Peninggalan Kolonial Belanda Sebagai Sumber Belajar Sejarah Lokal Jambi - Susnayanti Susnayanti; Junita Yosephine Sinurat (Prabayaksa: Journal of History Education, 2024)
The research aims to establish a historical understanding of the essential presence of historical heritage as an argument of the memories of Jambi itself especially during the Dutch Colonial period, reconstruct the historical foundation and continuity of Jambi City during the Dutch Colonial period with historical buildings, interpreting the tasks and contributions of the historical buildings of the Dutch Colonial period for the creation of the special character of the new generation of Jambi, and also formulating a joint policy regarding the efforts to preserve the material heritage of the listed historical buildings of the Dutch Colonial period in Jambi City. This study is a special historical research of local history that took place in Jambi City. based on the research category, then the method used is the historical method with some levels are heuristics, criticism, interpretation and historiography. after the research was carried out, then the findings produced are first, the colonial period buildings in Jambi City are sourced in their physical condition, some are currently maintained, not maintained, until they have been exchanged for other recent buildings. Secondly, the buildings can be used for local history upgrading, and thirdly, as an asset of Jambi territory in advancing the holiday zone, especially historical tourism.